Analysis of Factors that Influence Interest in Buying Consumer - Novianty, Rozalina; Koesomaningsih, Rachmawati; Sumiati, Sumiati; Puspita Dewi, Sangrila (Journal of World Science, 2022)
Introduction: Retail business development is increasing in Ngawi Regency, making the competition between these retail businesses even tighter. This condition makes businesses such as shops, markets, and supermarkets compete to attract consumers to buy shopping at their place of business. This study aims to analyze the effect of pricing, location, and diversity of products partially and simultaneously on consumer buying interest at Puspita Senja Shop in Kersoharjo Village, Geneng District, Ngawi Regency. Method: Research method using quantitative. To obtain research data, survey methods using a questionnaire to 97 respondents. The sampling technique used was purposive sampling. Data analysis uses multiple linear regression analysis. Result: The results of simultaneous hypothesis testing using the F test found that the Fcount = 76.557 > Ftable = 3.09 with a significant level of 0.000 <0.05. This shows that the independent variables consisting of pricing (X1), location (X2), and product diversity (X3) together (simultaneously) have a significant effect on consumer buying interest (Y). Conclusion: Price determination, location, and product diversity partially or simultaneously have a significant effect on consumer buying stake at Senja Puspita Shop in Kersoharjo Village, Geneng District, Ngawi Regency.